Study on Seismic Dynamic Response of Shallow-Buried Subway Station Structure and Ancillary Facilities - Peng, Miao; Cui, Wei Jian (Civil Engineering Journal, 2018)
Strong earthquakes can cause damages to structural members and also yield non-negligible damages to nonstructural facilities, the latter being closely related to earthquake-induced inertial forces. At present, the acceleration response regularity of shallow-buried subway station structure is not very clear. Using the finite-element software ABAQUS, a dynamic soil-structure interaction model for a two-story subway station structure is established. The distribution of the peak acceleration response of the structure is obtained, and the damage assessment of non-structural facilities is carried out based on the structural acceleration response. The results demonstrate that, in general, the peak acceleration responses of the subway station structure increase from lower to upper story levels, while the peak acceleration responses at the same height are practically equal. Moreover, the peak accelerations of a shallow-buried subway station structure are generally less than or close to the peak ground acceleration. Furthermore, the nonstructural facilities are slightly damaged when subjected to a peak bedrock input acceleration of 0.1 g, and moderately damaged under a peak bedrock input acceleration in the range 0.2 – 0.6 g. Based on the acceleration response characteristics, it is proposed that the peak surface acceleration can be used as an index to evaluate the damage of non-structural facilities in shallow-buried subway station structure, which is simple, practical and basically meets the precision requirements.